Study of the Vaporization Rate of Liquid Nitrogen by Small- and Medium-Scale Experiments - T. Olewski; L. Vechot; M.S. Mannan (Chemical Engineering Transactions, 2013)
Potentially severe consequences associated to accidental liquefied natural gas (LNG) spills have motivated a number of different studies, including experimental work, towards their prediction. Most of these studies focus on vapour dispersion, however there is limited information regarding source term of vapour formation, which includes liquid spill, pool spreading and liquid vaporization rate. The present work investigates the contribution of different heat transfer mechanisms to the vaporization rate of cryogenic liquid through the series of small and medium-scale, well-controlled and instrumented experiments performed with liquid nitrogen (LN2). The vaporization rate of LN2 was measured and correlated to the individual contributions of conductive, convective and radiative heat transfer. The experiments on convection showed that this heat transfer mode can play a significant role in the vaporization rate of the cryogenic liquid. In these set of experiments, its contribution to total heat flux to an LN2 pool spilled on a concrete surface was measured to be as high as 30 % after 10 min for moderate wind speed of 2-3 m.s-1. The experimental data also showed that the sidewalls of the liquid containment may play a key role in the resulting amount of convective heat transfer and indicates that walls or fences could be used as a good mitigation method.